MANAGEMENT OF THE EXTENSION FUNCTION OF UNIVERSITIES BEFORE VIRTUALITY - García García, Luis (Revista Arbitrada Formación Gerencial, 2024)
The demands of a globalized world and with extensive use of new information and communication technologies demand the creation of virtual organizations and require a new form of organizational management. The objective of this research was to evaluate the competencies for the management of the extension function in Venezuelan Public Universities (UPV) in the face of virtuality, in order to know the relevant aspects necessary to be transformed to adapt the management of the extension function to this stage. The research was non-experimental, descriptive in nature, supported by field work, using an empirical-inductive approach and a quantitative research method for data analysis and interpretation. The technique used was the survey, and the instrument was the questionnaire. The results obtained from the data processing and the bibliographic review carried out by the researcher allowed defining the competency profile of the manager of the extension function, both from the current perspective and the virtual perspective, and after contrasting both profiles, they were formulated guidelines in order to adapt the management profile, based on competencies, of the extension function of Venezuelan Public Universities in the face of virtuality. It was concluded that the Venezuelan Public Universities must assume the changes that are posed before virtuality, both in the foundations of the extension function and in the way of managing it, and thus meet the demands of increasing social inclusion with a high degree of quality and social relevance.